2018
DOI: 10.1002/chem.201704928
|View full text |Cite
|
Sign up to set email alerts
|

The Rickiols: 20‐, 22‐, and 24‐membered Macrolides from the Ascomycete Hypoxylon rickii

Abstract: In preceding studies the neotropical ascomycete Hypoxylon rickii turned out to be a prolific source of new secondary metabolites, considering that we had obtained terpenoids with five different scaffolds along with a series of terphenyls. From the mycelial extracts of a 70 L scale fermentation of this strain we additionally isolated nine new macrolides (1-9) by RP-HPLC. The planar structures were elucidated by NMR spectroscopy complemented by HR-ESIMS. The relative configurations were assigned by J-based confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

10
0

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…The main metabolite of the mono cultural extract of MUCL 54624 was identified by comparison of UV/Vis and MS data as rickiol A (8; Fig. 11E-F), previously described from H. rickii (Surup et al 2018b). Orthosporin (9; Quang et al 2002), daldinone B (10;Stadler et al 2008) was identified by comparison with an internal database in several strains of H. rubiginosum, H. perforatum and H. petriniae (cf.…”
Section: Hplc Profiling Of Stromatamentioning
confidence: 82%
“…The main metabolite of the mono cultural extract of MUCL 54624 was identified by comparison of UV/Vis and MS data as rickiol A (8; Fig. 11E-F), previously described from H. rickii (Surup et al 2018b). Orthosporin (9; Quang et al 2002), daldinone B (10;Stadler et al 2008) was identified by comparison with an internal database in several strains of H. rubiginosum, H. perforatum and H. petriniae (cf.…”
Section: Hplc Profiling Of Stromatamentioning
confidence: 82%
“…Biological activities of secondary metabolites from a diverse range of microorganisms have been demonstrated in many studies. Many studies have been done on the secondary metabolites of some antagonistic fungi and many antimicrobial compounds have been identified (Helaly et al, 2017;Richter et al, 2016;Surup et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The biological activity of metabolites 1 – 5 was assessed against a broad test panel of bacteria and fungi as well as the cell lines L929 and KB3.1 [ 10 ]. However, no inhibition was observed for the Gram-positive bacteria Bacillus subtilis , Micrococcus luteus , Mycobacterium sp., Staphylococcus aureus , the Gram-negative bacteria Chromobacterium violaceum , Escherichia coli , Pseudomonas aeruginosa , the filamentous fungus Mucor hiemalis , and the yeasts Candida albicans , Pichia anomala , Rhodotorula glutinis , and Schizosaccharomyces pombe up to 66 µg/mL.…”
Section: Resultsmentioning
confidence: 99%